From Glossy to Greasy: The Impact of Learned Associations on Perceptions of Food Healthfulness - Ye, Ning; Morrin, Maureen; Kampfer, Kristina (Journal of Consumer Psychology, 2020)
We demonstrate that consumers have learned that unhealthy snacks such as potato chips tend to be sold in glossy packages, whereas healthier snacks such as crackers tend to be sold in matte packages (in studies 1–3). As a result, consumers who see a snack food package with a glossy [matte] surface will infer lesser [greater] healthfulness of its contents (study 4), consume less [more] of it (study 5), and be more likely to choose a glossy [matte] package from an assortment of snack packages if motivated to engage in tasty [healthful] eating (study 6). Theoretical and managerial implications as well as future research opportunities are discussed.